Analisa Dan Desain Monitoring Pembangkit Listrik Tenaga Angin Dengan Menggunakan Web Dan Arduino - Chaniago, Bayu; Hamzah, Amir (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Wind is one of the energy that can be utilized as a power plant that can be developed in Indonesia. Wind speeds can change at any time result in wind turbine rotation and changes to voltage; therefore, a system that is able to monitor the changes that occur is required. The system used as a data storage is data logger. The data to be stored is data from how big the speed of the wind is and how much generator voltage generates. The wind speed will be detected by the anemometer sensor, and the voltage from the rectified AC generator to DC will be detected by the voltage sensor. Both sensors will be tested by comparing the results with digital wind speed measuring instruments and voltmeter, the result of the comparison yields 96.7% for the voltage sensor and 97% for the anemometer sensor based on simulation of 5 test data. The system uses arduino uno as data processing from anemometer sensor and voltage sensor. This data will be sent via GSM Shield and will be stored in the SQL database, and this data will also be stored on the SD card as backup storage if the signal from GSM is unstable. Then this data will be displayed on the website.Keywords : Anemometer sensor, Data Logger , Voltage sensor , Database SQL, Website